2014
DOI: 10.1002/2013ja019422
|View full text |Cite
|
Sign up to set email alerts
|

Hokkaido HF radar signatures of periodically reoccurring nighttime medium‐scale traveling ionospheric disturbances detected at short ranges

Abstract: The Super Dual Auroral Radar Network Hokkaido HF radar often detects periodically reoccurring E region echoing regions propagating toward or away from it. In this work, we consider 117 of such events identified for [2008][2009][2010][2011][2012]. These are shown to occur at nighttime, preferentially during summer, although significant number for events was found for winter. Statistics for the local time of occurrence, magnitude of the speed and polarity of progressions, and temporal and spatial periodicities a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 54 publications
4
12
0
Order By: Relevance
“…Several additional arguments supporting the notion of strong electrical coupling between the E and F regions during MSTID events have been identified. These include (1) F region echo velocity is consistent with the expected electric field direction within regions of depleted/enhanced electron density ), (2) E region plasma velocity is comparable to that in the F region (Koustov et al 2014), (3) polarity of the E region velocity changes consistently in neighboring regions with enhanced/depleted plasma density ), and (4) the power of E region echoes correlates with the measured Doppler velocity (Koustov et al 2014). However, there are also several outstanding issues, including (1) sometimes, the region of depleted plasma correlates with a sheared plasma flow of opposite polarities, instead of a single direction ) and (2) polarity of the velocity is inconsistent with that usually observed for MSTIDs over Japan with the middle and upper atmosphere (MU) VHF radar (although at quite different MLAT).…”
Section: Nighttime Mstids: E Region Signatures and Vertical Couplingsupporting
confidence: 54%
See 3 more Smart Citations
“…Several additional arguments supporting the notion of strong electrical coupling between the E and F regions during MSTID events have been identified. These include (1) F region echo velocity is consistent with the expected electric field direction within regions of depleted/enhanced electron density ), (2) E region plasma velocity is comparable to that in the F region (Koustov et al 2014), (3) polarity of the E region velocity changes consistently in neighboring regions with enhanced/depleted plasma density ), and (4) the power of E region echoes correlates with the measured Doppler velocity (Koustov et al 2014). However, there are also several outstanding issues, including (1) sometimes, the region of depleted plasma correlates with a sheared plasma flow of opposite polarities, instead of a single direction ) and (2) polarity of the velocity is inconsistent with that usually observed for MSTIDs over Japan with the middle and upper atmosphere (MU) VHF radar (although at quite different MLAT).…”
Section: Nighttime Mstids: E Region Signatures and Vertical Couplingsupporting
confidence: 54%
“…Ogawa et al (2009) suggested such a coincidence is indicative of electrodynamic coupling between these two regions in the form of a polarization electric field (Perkins 1973) which maps into the E region without attenuation, as envisioned theoretically (e.g., Yokoyama and Hysell 2010). Koustov et al (2014) performed a more comprehensive analysis of E region MSTID signatures in HOK echoes and reported preferential occurrence of such echoes in summer with a secondary maximum in winter. This tendency is despite the fact that E region nighttime HOK echoes are more frequent in winter (Yakymenko et al 2015).…”
Section: Nighttime Mstids: E Region Signatures and Vertical Couplingmentioning
confidence: 68%
See 2 more Smart Citations
“…These two directions look very similar to the corresponding Hok-F directions, but they are observed slightly later or earlier accordingly. The possibility of the southwestward or northwestward MSTIDs in the E region was reported by Koustov et al (2013), who had also used the Hokkaido radar data in their study. The southeast daytime peak is significantly weaker for Hok-E as compared to Hok-F (see azimuths~120°at~12 LT in Fig.…”
Section: Resultsmentioning
confidence: 91%